(untitled) (Al-Academy, 2024)
The research dealt with the elements of the tale in contemporary Iraqi painting (Khlaif Mahmoud as a model). Where the research problem was identified by answering the following question: - Are the elements of the tale achieved in the works of the artist Khalif Mahmoud?The research included four chapters, the first chapter dealt with the research problem, the research objective, and their objective, temporal and spatial limits. It followed by the terminology and procedural definition. Chapter two included the theoretical framework that contained three sections. The first dealt with the concept of the tale and its components, the second one dealt with the tale from linguistic narration to narration in contemporary Iraqi painting, while the third dealt with the foundations of the tale in painting and its perspectives for the artist Khlaif Mahmoud. Chapter three dealt with a presentation of the research procedures. As for chapter four, it included what was achieved of research procedures to reach the goals in light of the analysis of the approved samples, and the results came in which the artist relied on the style of modern realism and expressionism related to the popular heritage (the tale). The researcher also reached a number of conclusions, including that the tale is the product of a popular and cultural heritage that has been inherited by generations since the inception of creation and ended with the path and the biography of the artist.